Epithelioid trophoblastic tumor that requires fertility preservation: A case report and review of literature - Xue-qian Qian; Yuan-ming Shen; Xiao-yun Wan; Xing Xie (Elsevier, 2020)
Objective: Epithelioid trophoblastic tumor (ETT) is very rare and few cases have been published in the English literature. Hysterectomy is the recommended treatment, due to the high rate of recurrence and mortality. The objective of this article is to present a rare case of ETT with fertility-preserving treatment and review published similar cases. Case report: We report the case of ETT in a 19-year-old Chinese woman, who had a strong desire of fertility preservation. She presented with vaginal spotting and hysteroscopy showed an isolated solid mass (2.0 × 1.5 × 1.5 cm) at the right corner of the uterine cavity. Serum β-human chorionic gonadotropin (β-HCG) persisted at low level elevation about 100 IU/L. We treated her with a lesionectomy and 3 cycles EP-EMA (etoposide, cisplatin/etoposide, methotrexate and actinomycin) chemotherapy regimen. The patient is now in stable condition, without any signs of recurrence during 20 months of follow-up. Conclusion: Fertility-preserving surgery would probably be a feasible and safe strategy for the patients whose lesions can be completely removed.